Mekanisme Penyelesaian Sengketa Internal Partai Persatuan Pembangunan (PPP) Pasca Reformasi Mekanisme Penyelesaian Sengketa Internal Partai Persatuan Pembangunan (PPP) Pasca Reformasi - AfriLeonardo HasbiTasween (Jurnal Penelitian Hukum Legalitas, 2016)
Based on the provisions of the 1945 Constitution of the State of the Republic of Indonesia after the fourth amendment, described in Article 1 paragraph (1) and (2) namely that the State of Indonesia is a unitary State of the Republic, and Sovereignty is in the hands of the people and carried out according to Constitution. One of the noble principles in the 1945 Constitution emphasizes the guarantee of freedom of association as part of Human Rights, where Political Parties are one of the pillars of independence of the association The purpose of this research is to know and analyze the ideal idea which is done by the Government in the settlement of internal disputes of political party, especially the United Development Party (PPP) after the reformation, attributed to the increasing role of political party in the life of nation and state which is not followed by harmonious political communication, this is due to the frequent occurrence of debates that occur when they compete in the political field. The research method used is descriptive qualitative descriptive research using case study. The type of approach used in this research is the approach to empirical data in the field by involving two sources of evidence at the same time that is systemic interview and direct observation to the research which is also associated with Certainty Law.